2023
DOI: 10.3390/ijms24021329
|View full text |Cite
|
Sign up to set email alerts
|

The Bright Side of Psychedelics: Latest Advances and Challenges in Neuropharmacology

Abstract: The need to identify effective therapies for the treatment of psychiatric disorders is a particularly important issue in modern societies. In addition, difficulties in finding new drugs have led pharmacologists to review and re-evaluate some past molecules, including psychedelics. For several years there has been growing interest among psychotherapists in psilocybin or lysergic acid diethylamide for the treatment of obsessive-compulsive disorder, of depression, or of post-traumatic stress disorder, although re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 243 publications
0
1
0
Order By: Relevance
“…Classical (serotonergic) psychedelics have undergone a resurgence of interest for their potential to produce rapid and sustained therapeutic effects 1,2 . The therapeutic properties of psychedelics are being explored both preclinically and clinically, but studies have focused on a limited number of compounds 3,4 . Psychedelics may be limited by their hallucinogenic effects, which can cause confusion and anxiety in some patients, necessitating close clinical supervision.…”
mentioning
confidence: 99%
“…Classical (serotonergic) psychedelics have undergone a resurgence of interest for their potential to produce rapid and sustained therapeutic effects 1,2 . The therapeutic properties of psychedelics are being explored both preclinically and clinically, but studies have focused on a limited number of compounds 3,4 . Psychedelics may be limited by their hallucinogenic effects, which can cause confusion and anxiety in some patients, necessitating close clinical supervision.…”
mentioning
confidence: 99%
“…Further animal and human studies have shown that different efficacy at 5-HT2A receptors is a key pharmacological mechanism responsible for the psychedelic effects [22][23][24] and that different psychedelic substances also have affinities for other receptors: serotonergic, dopaminergic, glutamatergic, adrenergic, and histaminergic [25][26][27][28]. Psychedelic stimulation of 5-HT2A receptors disrupts the cortical rhythm and large-scale brain networks through an increase in neocortical neuron excitation and subsequent augmentation of extracellular glutamate release in the prefrontal cortex [21,29,30].…”
Section: The Mechanism Of Action Of Psychedelicsmentioning
confidence: 99%
“…Since the 1870s, the peyote cult has spread among the indigenous cultures of North America and is essential to the rituals of the Native American Church (NAC), founded in 1914 [98,99]. The plant is not conceived as a hallucinogen, but as a "teacher"; there is no distinction between medicine and religion, nor a separation between body and mind [100][101][102]. Thus, a special religious cult was created around peyote in the Native American Church (NAC) [102][103][104].…”
Section: Ethnopharmacologymentioning
confidence: 99%